PT Kereta Api Indonesia’s Crisis Communication Strategy on Instagram During the Flood Disaster in Operational Area 4 Semarang - Umiana Larasati; Diana Amalia (Lavish Opulent Education, 2026)
The rapid development of digital communication has transformed how organizations manage crisis communication, particularly through social media platforms. During crisis situations, organizations are required to provide fast, transparent, and responsive communication to maintain public trust and organizational reputation. This study aims to analyze the crisis communication strategy implemented by PT Kereta Api Indonesia (PT KAI) through its official Instagram account, @kai121_, during the flood disaster in Operational Area 4 Semarang in January 2026. This research employed a descriptive qualitative approach with an interpretive paradigm. The data were collected through documentation studies of Instagram content uploaded during the crisis period and analyzed using qualitative content analysis based on Situational Crisis Communication Theory (SCCT). The findings reveal that PT KAI implemented several crisis communication strategies, including excuse, justification, apology, compensation, and reminder strategies. The most dominant strategy identified was excuse, where PT KAI consistently explained that operational disruption was caused by external environmental factors such as flooding, heavy rainfall, and damaged railway infrastructure. The organization also emphasized passenger safety, provided operational updates, delivered apology messages, offered ticket refunds, and communicated recovery progress throughout the crisis period. In addition, Instagram played an important role as a visual and interactive communication platform that enabled PT KAI to maintain transparency and public engagement during the disaster. The study concludes that social media-based crisis communication has become an essential communication tool for public service organizations in maintaining public trust and supporting organizational recovery during crisis situations. The findings contribute to the development of digital crisis communication studies and provide practical insights for public relations practitioners in managing crisis communication through social media platforms.